Evolusi Konsep Kepemimpinan di Tempat Kerja : Kajian Literatur - Dinda Restiana; Mutiara Salsabila Haryani; Mutiara Salsadila; Netty Merdiaty (Pusat Riset dan Inovasi Nasional, 2025)
In recent years, the idea of leadership has changed dramatically to keep up with the quick advancements in technology, society, and the economy. Effective leadership has a direct impact on organizational productivity. A leader who properly manages human resources makes sure that workers are efficient and productive. Leaders create a positive work atmosphere, improve employee motivation, and give clear directions. Effective leadership increases productivity and helps organizations reach their objectives. Therefore, a leadership approach that emphasizes individual development is essential to enhancing overall organizational performance. In this study, the literature review approach is used. The results of this study of the literature suggest that inclusive, flexible, and technology-based leadership are all necessary for effective leadership in the current day. Employee engagement, well-being, and performance have all been demonstrated to improve under leadership that emphasizes personal growth and active team participation. Leadership that prioritizes technology utilization, interpersonal interactions, and change adaptation is essential to an organization's future success.